Projeto Logos II na Paraíba: ingerências políticas e implicações na sua Proposta Político-Pedagógica - Andrade, Jerusa Pereira de (1995)
The present work was done with the objective of investigating issues of our interest, aroused from the experience gained by the pedagogical practice adopted by Project Logos II. It is our intention here to show the analysis and interpretation of data on Project Logos II in Paraiba: political interferences and implications for its political-pedagogical proposal. By observing reality, it was possible to notice that political interferences had already entered the universe of rural area before affecting Project Logos II itself, bringing forth unprofessional teachers. The phenomenon of contracting the layperson, mainly women, for teaching activities rests upon the lack of trained teachers for the rural area as well as on the lack of motivation of the urban professional who finds it difficult to commute to the country to work. Within petty political network, the unprofessional teachers are handled during electoral periods and undervalued in their relations and conditions of work. Coming to Project Logos II, course designed to assist unprofessional teachers who work with the first four years of elementary school, those teachers are also subjected to political reprisal, caused by the person's revelation of the secret vote to the contractor. By giving room for political plots and allowing the admission to and stay of other individuals in the course, Project Logos II violates once more its pedagogical practice already made poor by the casuistry developed by public state and municipal powers that have planted the Project but do not offer the necessary resources for its fair functioning. There is a great number of unprofessional teachers in small towns and in the rural area. Project Logos II is usually the only choice for the acquisition of a profession and even for adults' schooling. For fear of Project Logos II may perish, due to the difficulties it has faced, the unprofessional teachers ask for help and give suggestions on a better assistance that might be offered by the course.